2001
DOI: 10.1037/0894-4105.15.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hypoxic risk in preterm birth infants: The influence of sex and severity of respiratory distress on cognitive recovery.

Abstract: The authors examined the differential effects of neonatal respiratory distress syndrome (RDS)--a condition associated with elevated risk for neonatal hypoxia-ischemia--on the cognitive development of the two sexes. The authors also attempted to establish whether the severity of respiratory distress is linked to cognitive outcome. Findings revealed an appreciable female advantage in cognitive recovery from RDS, yet the association between severity of RDS and outcome did not reach conventional statistical signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 57 publications
4
61
0
1
Order By: Relevance
“…Indeed, even if the normality of our preterm population was based on robust structural and clinical criteria, as in previous studies, 48,52 we cannot exclude the possibility that the sex related differences observed in the language and motor networks may have been caused by subtle cerebral lesions, because certain studies seem to suggest that preterm males may be more sensitive to brain injuries than females. 75,76 Therefore, it would be of interest to investigate whether these sex differences are also present in healthy term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even if the normality of our preterm population was based on robust structural and clinical criteria, as in previous studies, 48,52 we cannot exclude the possibility that the sex related differences observed in the language and motor networks may have been caused by subtle cerebral lesions, because certain studies seem to suggest that preterm males may be more sensitive to brain injuries than females. 75,76 Therefore, it would be of interest to investigate whether these sex differences are also present in healthy term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hormonal milieu may not fully account for sexual dimorphism in cerebral ischemia (Hurvitz et al, 1999;Vukmir, 2003). Emerging data suggests that cell death in brain may follow differing mechanistic paths depending on gender (Nunez et al, 2001;Lauterbach et al, 2001;Zhang et al, 2003;Schuessel et al, 2004), in addition to sex steroid exposure.…”
Section: Introductionmentioning
confidence: 99%
“…However, sexual dimorphism in human stroke risk persists well beyond the menopause (Sacco et al, 1998). Furthermore, female sex is associated with favorable outcome from ischemic stroke in children (Fullerton et al, 2003) and after brain injury in newborns (Lauterbach et al, 2001;Donders and Hoffman, 2002;Ingemarsson, 2003), suggesting that ovarian estradiol may not fully account for the female phenotype.…”
Section: Introductionmentioning
confidence: 99%